2007
DOI: 10.1590/s0100-40422007000500007
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição e especiação de mercúrio em sedimentos de áreas de garimpo de ouro do quadrilátero ferrífero (MG)

Abstract: Recebido em 17/2/06; aceito em 24/11/06; publicado na web em 2/7/07 DISTRIBUTION AND SPECIATION OF MERCURY IN SEDIMENTS FROM GOLD MINING SITES IN IRON QUADRANGLE (MINAS GERAIS). The concentration and thermodesorption speciation of mercury in sediments from four different Iron Quadrangle sites impacted by gold mining activity were determined. The mercury content of some samples was considerably high (ranging from 0.04 to 1.1 μg g -1 ). Only Hg 2+ was found and it was preferably distributed in the silt/clay frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
2
10
0
6
Order By: Relevance
“…It is estimated that gold exploration represents almost 70% of Hg released by anthropogenic sources in Brazil. 8 Other anthropogenic contribution occurs through prospecting, the electrolytic production of chlorine-soda, and the use of fossil fuels, waste incinerators, pigments, pesticides, mercury vapor lamps, batteries, and dental products. 9 All Hg compounds have high toxicity indexes concerning living organisms with organic Hg species being the most toxic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that gold exploration represents almost 70% of Hg released by anthropogenic sources in Brazil. 8 Other anthropogenic contribution occurs through prospecting, the electrolytic production of chlorine-soda, and the use of fossil fuels, waste incinerators, pigments, pesticides, mercury vapor lamps, batteries, and dental products. 9 All Hg compounds have high toxicity indexes concerning living organisms with organic Hg species being the most toxic.…”
Section: Introductionmentioning
confidence: 99%
“…9 Mercury determination in sediments is a useful tool to evaluate the impact in the aquatic environment. In some studies, 8,[11][12][13][14][15] Hg determination in sediment samples showed levels above of those allowed by the Brazilian legislation (0.17 µg g -1 ), according to level 1 from 2004 CONAMA Resolution 344 (Conselho Nacional do Meio Ambiente). 16 Windmöller et al, 8 High As levels in soil, sediment, and water can also be observed near gold exploration areas where the mineralogical occurrence of both metals is correlated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocorre naturalmente em formas orgânicas e inorgânicas, não só no estado sólido ou dissolvido, mas também na fase gasosa. Consequentemente, seu ciclo biogeoquími-co envolve processos que ocorrem no solo, na água e na atmosfera (WINDMÖLLER et al, 2007). Na superfície terrestre, o mercúrio é depositado no solo e em ambientes aquáticos.…”
unclassified
“…Diversas técnicas analíticas estão disponíveis para a análise de solos, como a espectrometria de massa com fonte de plasma indutivamente acoplado (iCP-ms) (milagres et al, 2007), a espectrometria de emissão atômica (iCP-aes) (milagres et al, 2007) e a espectrofotometria de absorção atômica (aas) (Windmöller et al, 2007); entre essas está a análise por ativação neutrônica (aan) (De soete et al, 1972;alfassi, 2000). a escolha de uma ou outra técnica depende das características do analito, como limites de detecção, exatidão e precisão.…”
unclassified